O respekcie dla moralnej mocy prawdy. Niedo− kończone rozmowy z ks. Tadeuszem Styczniem - SZOSTEK, Andrzej (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
A landmark in the output of Tadeusz Styczeń, SDS, was his lecture “Freedom in Truth,” published in 1988. It was there that Styczeń for the first time stated that the recognition of a truth, even of a most banal truth, is so binding for human freedom that a betrayal of any truth stated by the subject and recognized by him or her as true is a violence done to this personal subject, who is rational and free, and this is so regardless of any other harm such a betrayal of truth might trigger. This precious idea, inspired by the events from the Solidarity period in Poland deserves a gracious and critical continuation, which was difficult for Styczeń himself due to his deteriorating health. The author of the article points to the fact that stating a truth is inescapably connected to its valuation and to the recognition that at the given moment precisely this truth, out of an infinite number of possible truths, deserves being known and recognized as true. However, the attempt, undertaken by Styczeń, to derive personalism from his analysis of a cognitive act of truth knowing will fail unless it incorporates the experience of knowing the value of the person and his or her dignity, «given» to the subject to recognize. Thus the aim of an ethicist must be to combine the «inner» experience of the subject’s freedom being bound by the truth he or she has recognized with the «external» one, which consists in knowing the value of the recognized being, in particular of a personal being. Translated by Dorota Chabrajska